The nature of biology an introduction - Gardner, E. Ty; Boyd, Kyle
Why study biology? What's it all about? Why does it matter? This is the video that helps answer these common questions about biology. Images from the natural world reinforce the sense of wonder and excitement involved in studying life science. Interviews with science professionals help viewers appreciate the impact and value of biology in society. The program is organized around the general themes of biology: diversity of life, heredity, cells, interdependence of life, flow of matter and energy, and evolution of life. Through exploring these themes, students gain an understanding of the principles and values of life science.